Acquired epidermodysplasia verruciformis in an HIV positive child. Report of a case - Lourdes Rodríguez; Romina Contreras; Beatriz Di Martino Ortiz; Lourdes Bolla de Lezcano (Our Dermatology Online, 2015)
Epidermodysplasia verruciformis (EV) is a rare genodermatosis whose main feature is a genetic predisposition to persistent skin infection by different serotypes of human papillomavirus (HPV). In recent years, an EV-like syndrome has been described in patients with impaired cell-mediated immunity, including patients with HIV. We report the case of a teenage female patient with congenital infection with the human immunodeficiency virus (HIV), which has similar lesions to classical EV.